Quinoline-triazole half-sandwich iridium(III) complexes: Synthesis, antiplasmodial activity and preliminary transfer hydrogenation studies - Melis, Diana (Department of Chemistry, 2020)
Malaria is a devastating and pervasive infectious disease and continues to be a major global health issue, with over half the world's population being at risk of transmission. In the absence of a suitable vaccine, efforts to eradicate the disease rely heavily on clinically available drugs. Plasmodium falciparum, the deadliest species of malaria, has however become resistant to most conventional antimalarial treatments, resulting in the worldwide search for new, effective drugs. Amongst other requirements, these drugs should target resistant parasitic strains in an attempt to curb the escalation of the disease. In this regard, the incorporation of a metal into the organic framework of a biologically active compound has become an increasingly popular method of enhancing antiplasmodial activity in the drug-resistant parasite strains. Two series of 7-chloroquinoline-1,2,3-triazole ligands, one with the direct attachment of the triazole to the quinoline and one where the two entities are separated by an aminopropyl linker, were synthesised. Coordination of selected ligands with [IrCl(μ-Cl)(Cp*)]₂ yielded six neutral, cyclometallated and two cationic,N,N-chelated iridium complexes. Computational analysis revealed that metal coordination to the quinoline nitrogen occurs first, forming an unstable kinetic product that, upon heating over time, forms the stable, cyclometallated, thermodynamic product. All of the compounds were fully characterised using an array of spectroscopic (¹H, ¹³C{¹H}, ¹⁹F{¹H}, ³¹P{¹H} NMR and FT-IR spectroscopy) and analytical (mass spectrometry and melting point analysis) techniques. Single crystal X-ray diffraction confirmed the proposed molecular structure and a pseudo-tetrahedral geometry around the metal centre for the cyclometallated and monodentate, quinoline nitrogen-coordinated complexes. The ligand series containing the propyl chain linker displayed superior in vitro antiplasmodial activity against the chloroquine-sensitive NF54 strain of P. falciparum in comparison with the series having thetriazole directly attached to the quinoline moiety. Upon complexation with iridium, the activity of selected ligands is significantly enhanced (0.247< IC₅₀ (μM)< 2.34), with some complexes being over one hundred times more active than their respective ligands. For most of these compounds, their antiplasmodial activity is lower in the chloroquine-resistant K1 strain, however, their calculated RI values suggest that they likely only experience mild cross-resistance, not to the same extent of chloroquine. Selected complexes were tested against the healthy, mammalian Chinese Hamster Ovarian (CHO) cell line and were found not to be cytotoxic. They were also determined to be more selective towards the parasite than healthy cells. An “IC₅₀ speed assay” using the three most active complexes against the chloroquine-sensitive NF54 strain found the two neutral, cyclometallated complexes to be fast-acting compounds which reach their lowest IC₅₀ values within 24 hours, while the active cationic complex was determined to be slow-acting, only reaching its lowest IC₅₀ value after 48 hours. To gain insight into the possible mechanisms of action of these compounds, selected ligands and complexes were tested for their ability to inhibit the formation β-haematin(the synthetic form of haemozoin), sinceone of the mechanisms of 7-chloroquinoline-containing compounds is the inhibition of haemozo information. All five of the tested compounds were found to inhibit β-haematin formation to some extent but were, in general, less effective β-haematin inhibitors than chloroquine itself. Interestingly, the aminopropyl-containing cationic complex which displayed the lowest antiplasmodial activity exhibited far greater β-haematin inhibitory activity (IC₅₀ 9.65 μM) than chloroquine(IC₅₀ 65.3 μM).Finally, three of the most active complexes were evaluated for their ability to facilitate transfer hydrogenation, by reducing β-nicotinamide adenine dinucleotide (NAD+) to NADH in the presence of hydrogen source, sodium formate. Through preliminary qualitative and quantitative cell-free experiments, it was found that the two most active neutral, cyclometallated complexes tested may be capable of acting as transfer hydrogenation catalysts while the active, cationic complex tested did not indicate reduction of NAD+ to NADH over 4 hours.